2016
DOI: 10.7196/samj.2016.v106i6.10274
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic thrombocytopenic purpura in the presence of connective tissue disease and HIV infection: A diagnostic and therapeutic challenge in a resource- constrained setting

Abstract: Thrombotic thrombocytopenic purpura is a catastrophic disease and may occur in the presence of other confounding diseases. We present a case of TTP in a patient with connective tissue disease and HIV infection, in whom the diagnosis and management of TTP was challenging. It is important to understand the various underlying mechanisms that drive TTP in the presence of these comorbid diseases, so that an appropriate treatment strategy can be initiated. Our patient failed an initial trial of plasma infusion alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…In contrast, to reports of TTP in other parts of the world, in this study, TTP was most commonly secondary to, or associated with, HIV infection ( n = 32/41,78.0%). This finding confirms the association of HIV in other previous South African studies . Similarly, in this study, HIV associated TTP was reported predominantly in African females with advanced HIV disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, to reports of TTP in other parts of the world, in this study, TTP was most commonly secondary to, or associated with, HIV infection ( n = 32/41,78.0%). This finding confirms the association of HIV in other previous South African studies . Similarly, in this study, HIV associated TTP was reported predominantly in African females with advanced HIV disease.…”
Section: Discussionsupporting
confidence: 93%
“…This finding confirms the association of HIV in other previous South African studies. 4,5,15 Similarly, in this study, HIV associated TTP was reported predominantly in African HIV induces cytokine production, namely tumour necrosis factor-α, interleukin −1, and −6, 16 as well as von Willebrand factor (VWF) and tissue factor expression, 17 which results in endothelial cell dysfunction. In HIV-associated TTP, chronic inflammation results in microthrombi production because of endothelial injury, activation of the coagulation cascade and VWF multimer release.…”
Section: Discussionsupporting
confidence: 55%
“…TTP is a rare, potentially fatal illness that affects less than 0.5% of individuals diagnosed with SLE [ 7 , 8 ]. Although the pentad of severe thrombocytopenia, fever, neurological problems, renal insufficiency, and microangiopathic hemolytic anemia was initially described in 1924, it was not until 1966 that it was published [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that individuals who have acquired TTP as a result of SLE typically have lower levels of ADAMTS13 in their blood [ 7 ]. This is because they develop autoantibodies against the enzyme, which cleaves large precursors of VWF into smaller units that have less adhesive surface area for platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation